Keyword extraction using a back propagation network and rule extraction - Liu, Michael David S. (Animo Repository, 2010)
Keyword extraction is vital for Knowledge Management Systems, Information Re- trieval Systems, and Digital Libraries as well as for general browsing of the web. Keywords are often the basis of document processing methods such as clustering and retrieval since processing all the words in the document can be slow. Common models for automating the process of keyword extraction are usually done by using several statistics-based methods such as Bayesian, K-Nearest Neighbour, and Expectation-Maximization. These models are limited by word-related features that can be used since adding more features will make the models more complex and difficult to comprehend. In this research, a Neural Network, specifically a backpropagation network, will be used in generalizing the relationship of the title and the content of articles in the archive by following word features other than TF-IDF, such as position of word in the sentence, paragraph, or in the entire document, and formats such as heading, and other attributes defined beforehand. In order to explain how the backpropagation network works, a rule extraction method will be used to extract symbolic data from the resulting backpropagation network. The rules extracted can then be transformed into decision trees per- forming almost as accurate as the network plus the benefit of being in an easily comprehensible format.